2015
DOI: 10.3892/mmr.2015.4623
|View full text |Cite
|
Sign up to set email alerts
|

Capsaicin enhances anti-proliferation efficacy of pirarubicin via activating TRPV1 and inhibiting PCNA nuclear translocation in 5637 cells

Abstract: The recurrence of bladder cancer after surgery with or without chemotherapy remains a major challenge in bladder cancer treatment. Previous studies have shown that transient receptor potential vanilloid 1 (TRPV1) acts as a tumor suppressor through inducing apoptosis in bladder cancer cells. However, whether activation of TRPV1 has any synergistic effects with pirarubicin (THP), one of main drugs used in urinary bladder instillation chemotherapy to improve chemotherapeutic efficacy has remained elusive. The pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(38 citation statements)
references
References 37 publications
(36 reference statements)
0
37
0
1
Order By: Relevance
“…This finding was in accordance with the results of Vercelli et al,43 who demonstrated a significant decrease in the cell growth rate of MCF-7 breast cancer cells upon capsaicin stimulation. Interestingly, Zheng et al44 furthermore showed that capsaicin was capable of enhancing the antineoplastic effects of pirarubicin, which is an analog of the antibiotic doxorubicin 45. In HCT116 cells, the inhibition of cell proliferation by TRPV1 signaling was demonstrated as well.…”
Section: Discussionmentioning
confidence: 99%
“…This finding was in accordance with the results of Vercelli et al,43 who demonstrated a significant decrease in the cell growth rate of MCF-7 breast cancer cells upon capsaicin stimulation. Interestingly, Zheng et al44 furthermore showed that capsaicin was capable of enhancing the antineoplastic effects of pirarubicin, which is an analog of the antibiotic doxorubicin 45. In HCT116 cells, the inhibition of cell proliferation by TRPV1 signaling was demonstrated as well.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the treatment of stomach cancer cells with a combination of cisplatin and capsaicin caused greater than apoptosis than either of these agents given singly [11, 12]. A similar effect was also observed when capsaicin was given in combination with the doxorubicin analog pirarubicin [13]. The present manuscript investigates for the first time the anti-cancer activity of the combination of capsaicin and camptothecin.…”
Section: Introductionmentioning
confidence: 73%
“…Subsequent to the first investigations into polymer-controlled drug release in cancer therapy (8,24,25), the field has rapidly expanded and applied to the treatment of other diseases (18,26,27). Aliphatic polyesters, particularly PLGA, have been extensively explored for local drug delivery.…”
Section: Discussionmentioning
confidence: 99%
“…Preparation of PPC polymer loaded with sirolimus. Various ratios of PPC and sirolimus were used to produce PPC-sirolimus polymers and cell growth experiments, performed by MTT assay as previously described (18), demonstrated that the polymer made with 900 mg PPC and 100 mg sirolimus resulted in the greatest cell inhibitory effect; therefore, this ratio was used in the present study. The polymer solution was as follows: 1,000 mg PPC alone (PPC polymer) or 900 mg PPC plus 100 mg sirolimus (PPC-sirolimus polymer) was dissolved in 10 ml acetonitrile following stirring for 6 h. Electrospinning was performed using the electrospinning apparatus (Model ET2535; Beijing Ucalery Technology and Development Co., Ltd., Beijing, China).…”
Section: Methodsmentioning
confidence: 99%